2015
DOI: 10.1016/j.icarus.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined structural and compositional evolution of planetary rings due to micrometeoroid impacts and ballistic transport

Abstract: We introduce improved numerical techniques for simulating the structural and compositional evolution of planetary rings due to micrometeoroid bombardment and subsequent ballistic transport of impact ejecta. Our current, robust code is capable of modeling structural changes and pollution transport simultaneously over long times on both local and global scales. In this paper, we describe the methodology based on the original structural code of Durisen et al. (1989, Icarus 80, 136-166) and on the pollution trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…The required high ejection speeds are consistent with data from previous theoretical studies (22) and have been observed in laboratory experiments (impact jetting) (41,42). The ejection speed is likely to be larger for smaller ejecta (43,44), implying much higher ejection speeds for nanograins than for micrometer-sized and larger ejecta, which fuel the ballistic transport (10,15).…”
Section: Nanograin Dynamicssupporting
confidence: 88%
See 1 more Smart Citation
“…The required high ejection speeds are consistent with data from previous theoretical studies (22) and have been observed in laboratory experiments (impact jetting) (41,42). The ejection speed is likely to be larger for smaller ejecta (43,44), implying much higher ejection speeds for nanograins than for micrometer-sized and larger ejecta, which fuel the ballistic transport (10,15).…”
Section: Nanograin Dynamicssupporting
confidence: 88%
“…The radial density profile of the rings is shaped by various dynamical processes, including viscous spreading, resonances with satellites, intrinsic instabilities, and ballistic transport (5, 9-13) of ejecta released by impacts of interplanetary dust particles on the rings (14). The latter process is primarily responsible for redistributing and mixing the icy and non-icy material across the rings, as well as for the formation of sharp inner A and B ring edges (10,15).…”
mentioning
confidence: 99%
“…The ring mass has implications for the age of the rings (59). Traditional age estimates of Saturn's ring-satellite system fall into three categories: dynamical estimates based on the rate of recession of the small satellites from the rings due to gravitational torques, and the back-reaction on the A ring (10,60); structural evolution timescales based on the evolution of unconfined edges such as the inner edges of the A and B rings (11); and compositional timescales based on the assumption that the rings were formed as pure water ice and have subsequently been steadily darkened by the infall of interplanetary debris (9). Most of these timescale estimates depend, directly or indirectly, on the mass of the rings; both dynamical and compositional considerations suggest that low-mass rings are likely to be young and both approaches yield evolutionary ages ~10 8 yrs for the A and B rings, assuming the Voyager measurements of ring masses and interplanetary impact fluxes (59).…”
Section: Mass and Age Of Saturn's Ringsmentioning
confidence: 99%
“…Moses 1992;Feuchtgruber et al 1997;Moses et al 2000;Frankland et al 2016;Moses & Poppe 2017), the injection of metallic species into planetary magnetospheres (Christon et al 2015); the spatial and compositional evolution of Saturn's main ring system (e.g. Durisen et al 1989;Cuzzi & Estrada 1998;Estrada et al 2015); and the production of impact ejecta clouds and/or rings from airless bodies, like planetary satellites (e.g. Verbiscer et al 2009;Hedman et al 2009;).…”
Section: Edgeworth-kuiper Belt Dustmentioning
confidence: 99%